POTENTIAL EXTRACT of PARE FRUIT (Momordica charantia) AGAINST DIFFERENTIAL LEUKOCYTE IN CARP (Cyprinus carpio) WHICH INFECTED WITH Aeromonas hydrophila - Sri Andayani; Ellana Sanoesi; Oktaviani Setya (Journal of Fish Health, 2021)
Carp (C. carpio) in intensive production causes fish to be susceptible to disease, one of which is caused by A. hydrophila bacteria. Prevention is often done by giving synthetic chemical antibiotics that can be left in fish meat. Another alternative is to offer natural ingredients, one of which is bitter melon. The aim of the study was to determine the effect of bitter melon extract (M.charantia) on differential leukocytes (lymphocytes, monocytes and neutrophils) in carp (C. carpio) infected with A. hydrophila bacteria. This research method used a completely randomized design (CRD) with 4 treatments and 3 replications. The treatments used were the administration of different extract doses, namely: treatment A (550 ppm), treatment B (650 ppm), treatment C (750 ppm), and treatment D (850 ppm). positive (K+) with bacterial infection of 107 cells/ml and administration of antibiotics chloramphenicol 0.03 mg/L and negative control (K-) with bacterial infection of 107 cells/ml. Blood collection when the fish are healthy, after offering the bitter gourd extract and after being infected. The results showed that bitter melon extract had a significantly different effect on leukocyte differential. The highest value obtained from treatment D (850 ppm) with the percentage of lymphocytes (18.67-28)%. neutrophils (2.32 = 6.0)% and monocytes (21-26.67)%. In conclusion, treatment with D dose of 850 ppm used as an immunostimulant can increase the differential leukocytes.